Benefits and Challenges of Enterprise Architecture Use in Organizations - Mansurova, Dinara; Šebesta, Michal; Bruckner, Tomáš, 1974-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
This thesis deals with the topic of benefits and challenges of Enterprise Architecture (EA) use in organizations. The main objective of this thesis is the critical analysis of EA potential use in sample organization by examining its benefits and challenges, which results in form of recommendations necessary for efficient management of the organization using EA. Firstly, the thesis introduces the topic of EA along with its core concepts and principles. Then, the author discusses main drivers for EA and its typical application. Perceived in the field of EA benefits and challenges are identified and classified. The result is then confronted with a practical case study, which describes EA application in a sample organization. The author conducts the experimental EA initiative in that organization, by modeling current state (as-is) and potential solution architectures. The main deliverable of this initiative for the organization is the critical analysis of potential EA use within the organization with the identification of its added value and challenges. The findings are then summarized in form of recommendations for the future development of information systems of the organization.
Vedoucí práce: Michal Šebesta
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses